HOW CROATIAN FARMERS PERCEIVE AND ADAPT TO CLIMATE CHANGE- PRELIMINARY RESEARCH RESULTS (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Climate change presents a significant challenge to the agricultural sector, necessitating a thorough understanding of farmers’ perceptions and adaptation strategies for effective public policy development. A survey of 100 family farms in Croatia demonstrated a high level of awareness among farmers regarding the threats posed by climate change to ecosystems, biodiversity, and food security. They emphasized the need for more concrete government action and acknowledged substantial economic losses. While there is a consensus on the importance of climate-friendly agricultural practices, concerns persist regarding insufficient awareness of climate change risks. Common adaptation strategies employed by farmers include green manuring, the cultivation of resilient crops, and the implementation of irrigation systems. Income and education levels were shown to influence the adoption of these measures, highlighting the significant role of socioeconomic factors in adaptation. Farmers recognize the direct impact of climate change on their livelihoods and the urgency for action. The survey underscored the necessity for enhanced farmer education on climate change risks and the promotion of climate-friendly practices. Furthermore, the government must implement more decisive policies to support farmers in their adaptation efforts. To ensure the generalizability of these findings, further research using a more representative sample is recommended. This will facilitate a more comprehensive understanding of the challenges faced by Croatian farmers and contribute to the development of effective climate change adaptation strategies.